Implementation of Person Center Maternal Care in Midwifery Care Service: Scoping Review - Nastiti Aryudaningrum; Asri Hidayat (P3M Universitas 'Aisyiyah Surakarta, 2023)
A midwife has the best role and opportunity in providing midwifery care services and promotion of Maternal Child Health (MCH). Midwifery care is conducted by placing women as partners with a holistic understanding, as a good experience for their physical, psychological, emotional, social, cultural, spiritual, and reproductive health. This review aims to observe scientific research related to characteristics as well as perspectives on personcentered maternal care implementation in midwifery care service. Method: This scoping review was conducted by identifying the review questions by using PEOS framework; identifying relevant article based on inclusion and exclusion criteria; searching article by database; selecting article by using PRISMA Flowchart plot. Result: Based on 10 selection article, 7 articles is obtained A score and the 3 other articles get B score. Furthermore, there are 2 obtained themes, namely the importance and the characteristic of PCMC. Conclusion: The importance thing in each midwifery service implements the care based on Person Centered Maternal Care. PCMC characteristic is providing responsive, supportive care of client, conducting good communication, and providing autonomy to client for determining the choice. Midwifery as care providers should make improvement in the services so that client obtains a good experience in every maternal care provided.